Generating Bovine Monocyte-Derived Dendritic Cells for Experimental and Clinical Applications Using Commercially Available Serum-Free Medium - Guinan, Jack; Lopez, Brina S. (Frontiers in Immunology, 2020)
Advances in fundamental and applied immunology research often originate from pilot studies utilizing animal models. While cattle represent an ideal model for disease pathogenesis and vaccinology research for a number of human disease, optimized bovine culture models have yet to be fully established. Monocyte-derived dendritic cells (MoDC) are critical in activating adaptive immunity and are an attractive subset for experimental and clinical applications. The use of serum-supplemented culture medium in this ex vivo approach is undesirable as serum contains unknown quantities of immune-modulating components and may induce unwanted immune responses if not autologous. Here, we describe a standardized protocol for generating bovine MoDC in serum-free medium (AIM-V) and detail the MoDC phenotype, cytokine profile, and metabolic signature achieved using this culture methodology. MoDC generated from adult, barren cattle were used for a series of experiments that evaluated the following culture conditions: medium type, method of monocyte enrichment, culture duration, and concentration of differentiation additives. Viability and yield were assessed using flow cytometric propidium iodide staining and manual hemocytometer counting, respectively. MoDC phenotype and T cell activation and proliferation were assessed by flow cytometric analysis of surface markers (MHC class II, CD86, CD14 and CD205), and CD25 and CFSE respectively. Cytokine secretion was quantified using a multiplex bovine cytokine panel (IL-1α, IL-1β, IL-8, IL-10, IL-17A, IFN-γ, MIP-1α, TNF-α, IL-4). Changes in cell metabolism following stimulation were analyzed using an Extracellular Flux (XFe96) Seahorse Analyzer. Data were analyzed using paired t-tests and repeated measures ANOVA. Immature MoDC generated in serum-free medium using magnetic-activated cell sorting with plate adhesion to enrich monocytes and cultured for 4 days have the following phenotypic profile: MHC class II+++, CD86+, CD205++, and CD14-. These MoDC can be matured with PMA and ionomycin as noted by increased CD86 and CD40 expression, increased cytokine secretion (IL-1α, IL-10, MIP-1α, and IL-17A), a metabolic switch to aerobic glycolysis, and induction of T cell activation and proliferation following maturation. Cultivation of bovine MoDC utilizing our well-defined culture protocol offers a serum-free approach to mechanistically investigate mechanisms of diseases and the safety and efficacy of novel therapeutics for both humans and cattle alike.